Oncologic outcomes in patients treated with endoscopic robot assisted simple enucleation (ERASE) for renal cell carcinoma: Results from a tertiary referral center. Issue 10 (October 2019) - Mari, Andrea; Di Maida, Fabrizio; Tellini, Riccardo; Campi, Riccardo; Sforza, Simone; Cocci, Andrea; Siena, Giampaolo; Vittori, Gianni; Tuccio, Agostino; Masieri, Lorenzo; Lapini, Alberto; Raspollini, Maria Rosaria; et al.
Abstract: Introduction: Open Simple Enucleation (OSE) has been demonstrated to be an oncologically safe alternative to standard partial nephrectomy. We assessed the mid-term oncologic outcomes and predictors of disease recurrence in patients treated with Endoscopic Robot-Assisted Simple Enucleation (ERASE) verified through a standardized reporting system at a single institution. Material and methods: The clinical data of patients treated with ERASE for renal cell carcinoma at our Institution from January 2012 to September 2018 were retrospectively reviewed. Surface-Intermediate-Base (SIB) score was evaluated immediately after surgery. Patients with a ≥2 SIB score were excluded. The local and distant recurrence rates, the recurrence-free (RFS), cancer-specific (CSS) and overall (OS) survival were assessed. Kaplan-Meier and log-rank test were used to estimate survivals and to compare recurrence-free survival. Results: Overall, 259 patients were considered eligible for the present study. The median PADUA score was 7 (interquartile range [IQR] 6–9). Positive surgical margins (PSM) were registered in 7 (2.7%) cases. Median (IQR) follow-up time was 36 (27–51) months. Overall, 4 (1.5%) patients experienced systemic recurrence (SR) and 5 (1.9%) patients experienced local recurrence alone (LR) of whom 3 (1.1%) were on tumor resection bed, and 2 (0.8%) experienced recurrence elsewhere in the ipsilateral kidney. The 5-year RFS, CSS and OS were 94.2%, 98.9% and 93.6%, respectively. Higher nucleolar grade and PSM were the two factors significantly associated with worse RFS. Conclusions: ERASE is a safe procedure, achieving negative surgical margins in the vast majority of patients and providing excellent mid-term local control and oncologic outcomes.